Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð°Ñ†Ð¸Ð¸ ÑÑ‚Ð¸Ð»ÐµÐ½Ð³Ð»Ð¸ÐºÐ¾Ð»Ñ Ð½Ð° Ð¿Ñ€Ð¾Ð½Ð¸Ñ†Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½ Ð¾Ð´Ð½Ð¾- Ð¸ Ð´Ð²ÑƒÑ…ÐºÐ»ÐµÑ‚Ð¾Ñ‡Ð½Ñ‹Ñ… ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð¾Ð² Ð¼Ñ‹ÑˆÐ¸ - Pishko, O. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The permeability coefficients for one- and two-cell embryos for ethylene glycol (EG) and water molecules using the volumetry method and physical-chemical model, describing the mass exchange processes between a cell and its environment, were determined. The cleavage was shown as not affecting the transport characteristics of membranes, but augmenting their resistance to the increased cryoprotectant concentration effect.